Cerebral folate deficiency, developmental difficulties in autism spectrum disorder and the role of leucovorin: a narrative review of mechanisms and clinical evidence - Krittisak Anuroj (Drugs in Context, 2026)
Cerebral folate deficiency (CFD) has recently emerged as a potentially relevant contributor to developmental difficulties in a subset of individuals with autism spectrum disorder (ASD). CFD is characterized by reduced central nervous system folate availability despite adequate systemic folate status and has been commonly linked to folate receptor-α autoantibodies (FRAAs), which impair folate transport across the choroid plexus. Disruption of folate-dependent one-carbon metabolism may adversely affect neurodevelopment through multiple mechanisms. Leucovorin (folinic acid) represents a potential therapeutic option for CFD associated with FRAAs, and interest in its clinical use has grown in recent years. This narrative review summarizes the biological mechanisms linking CFD to developmental disturbances in ASD and synthesizes current clinical evidence regarding the use of leucovorin as a therapeutic intervention. Despite a compelling mechanistic basis, clinical evidence remains limited. Long-term safety and efficacy data are lacking, and existing studies have rarely incorporated biologically informed patient selection or biomarker-based stratification, whilst the inherent heterogeneity of ASD further complicates interpretation of treatment outcomes. Larger, well-designed studies are necessary to determine the intervention’s efficacy and identify responsive sub-groups, thereby informing clinical practice. Nevertheless, given the limited developmental window during which treatment for CFD would offer tangible developmental benefits and the inaccessibility of laboratory evaluations for CFD or FRAA positivity in many settings, this review also discusses an alternative pragmatic approach involving a therapeutic trial through shared decision making. Download the Plain Language Summary of this article: https://www.drugsincontext.com/plain-language-summaries/plain-language-summary-cerebral-folate-deficiency-developmental-difficulties-in-autism-spectrum-disorder-and-the-role-of-leucovorin-a-narrative-review-of-mechanisms-and-clinical-evidence